High-risk malignant melanoma: Value of chemotherapy with DTIC - Priario, Julio C.; Borges, Freddy; Levin, Roberto (Cirugía del Uruguay, 1982)
The prognosis of malignant melanoma is generally bad due to the frequency of metastatic lesions. These are more common in patients with trunk melanoma, and/or those with III, IV and V Clark's levels where there is high lymphnode involvement. These cases are referred to as high risk melanomas. Coadjuvant treatment with D.T.I.C. has been attemped in these patients. No improvement in the total survival time neither in the time free of disease was noticed by the "melanoma group" of the W.H.O. The prognostic importance of lymphnode involvement and the indication of prophylactic lymphnode emptying are discused. The authors conclude that the right resection of the primary tumor is the basic treatment, but it is neccesary to keep on the search for better coadiuvant procedures to improve surgical results.